Design and Implementation of a Software Defined Ionosonde. A contribution to the development of distributed arrays of small instruments - Floer, Markus (UiT Norges arktiske universitet, 2020)
In order to make advances in studies of mesoscale ionospheric phenomena, a new type of ionosonde is needed. This ionosonde should be relatively inexpensive and small form factor. It should also be well suited for operation in a network of transmit and receiver sites that are operated cooperatively in order to measure vertical and oblique paths between multiple transmitters and receivers in the network. No such ionosonde implementation currently exists. This thesis describes the design and implementation of a coded continuous wave ionosonde, which utilizes long pseudo-random transmit waveforms. Such radar waveforms have several advantages: they can be used at low peak power, they can be used in multi-static cooperative radar networks, they can be used to measure range-Doppler overspread targets, they are relatively robust against external interference, and they produce relatively low interference to other users that share the same portion of the electromagnetic spectrum. The new ionosonde design is thus well suited for use in ionosonde networks. The technical design relies on the software defined radio paradigm and the hardware design is based on commercially available inexpensive hardware. The hardware and software implementation is shown to meet the technical and scientific requirements that were set for the instrument. The operation of the instrument is demonstrated in practice in Longyearbyen, Svalbard. With this new ionosonde design and proof of concept implementation, it has been possible to re-establish routine ionospheric soundings at Longyearbyen, Svalbard; to replace the Dynasonde instrument that was decommissioned several years ago. It is also possible to use this new design as a basis for larger networks of ionosondes. The software and hardware design is made publicly available as open source, so that anyone interested can reproduce the instrument and also contribute to the project in the future.